1986
DOI: 10.2307/1510360
|View full text |Cite
|
Sign up to set email alerts
|

Initial Learning and Transfer Effects of Microcomputer Drills on LD Students' Multiplication Skills

Abstract: Although application of microcomputer-assisted instruction with learning disabled students is rapidly expanding, only limited research is available on the efficacy of such instruction. The primary purpose of this single-subject design study was to investigate whether learning of multiplication tables via computer programs transfers to paper-and-pencil tasks. Three male and three female fourth-grade LD students participated in the three phases of the study: baseline, microcomputer-assisted instruction, and tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1986
1986
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…But, again, details of the instructional delivery systems were incomplete, making implementation problematic. Finally, Chiang (1986) found benefits for CAI programs that included a skill-building component.…”
mentioning
confidence: 99%
“…But, again, details of the instructional delivery systems were incomplete, making implementation problematic. Finally, Chiang (1986) found benefits for CAI programs that included a skill-building component.…”
mentioning
confidence: 99%
“…A number of educators (e.g., Chiang, 1986;Lieber & Semmel, 1985;Romanczyk, 1986) have noted that research has not clearly validated the relative effectiveness of CAI as opposed to TA instruction. A few studies have begun to address this promise, but the claim is too broad to lend itself to precise empirical investigation (Clark, 1983), as instruction consists of multidimensional variables that are difficult to control.…”
Section: Promise 4: Microcomputer Instruction Can Be Superior To Tradmentioning
confidence: 99%
“…They found that word recognition speed could increase via CAP with a program using a repeated readings format. Chiang ( 1986) has provided evidence that drill and practice using the microcomputer also can be effective for teaching multiplication facts. Using 4-minute timings and a software program, Treasure Hunt, over a period of 12 days, Chiang demonstrated that students transferred the skills practiced on the computer to paper-and-pencil tasks.…”
Section: Representative Studiesmentioning
confidence: 99%
See 2 more Smart Citations